"Who will stand up for us?" the social determinants of health of women tea plantation workers in India - Preety R. Rajbangshi; Devaki Nambiar (BMC, 2020)
Abstract Introduction The tea estate sector of India is one of the oldest and largest formal private employers. Workers are dependent on plantation estates for a range of basic services under the 1951 Plantation Labour Act and have been subject to human rights violations. Ad hoc reports related to poor health outcomes exist, yet their determinants have not been systematically studied. This study in Assam, situated in Northeast India, sought to understand the Social Determinants of Health (SDH) of women plantation workers with an aim to offer directions for policy action. Methods As part of a larger qualitative study, 16 FGDs were carried out with women workers in three plantations of Jorhat district covering permanent and non-permanent workers. Informed consent procedures were carried out with all participants individually. Data were analyzed thematically using Ritchie and Spencer's framework based on an adapted conceptual framework drawing from existing global conceptual models and frameworks related to the SDH. Results Determinants at structural, intermediary and individual levels were associated with health. Poverty and poor labour conditions, compounded by the low social position of women in their communities, precluded their ability to improve their economic situation. The poor quality of housing and sanitation, inadequate food and rations, all hampered daily living. Health services were found wanting and social networks were strained even as women were a critical support to each other. These factors impinged on use of health services, diet and nutrition as well as psychosocial stress at the individual level. Conclusion Years of subjugation of workers have led to their deep distrust in the system of which they are part. Acting on SDH will take time, deeper understanding of their relative and/or synergistic contribution, and require the building of stakeholdership. Notwithstanding this, to have heard from women workers themselves has been an important step in visibilizing and building accountability for action on the health and SDH of women in plantation estates.